Implementation of Nginx Server with RTMP Module for Tea Leaf Maturity Monitoring - Yusuf, Mirza Ali; Ibnugraha, Prajna Deshanta; Sani, Muhammad Ikhsan (Syntax Corporation, 2024)
This research focuses on the application of Nginx Server to monitor the ripeness level of tea leaves in real-time using RTMP module and IP camera. In the tea industry, monitoring the ripeness of tea leaves is essential to ensure the quality of the final product. To achieve this goal, a system was built using Nginx as the main server that manages the real-time video transmission of IP cameras installed in tea plantations. The RTMP module is used to transmit streaming video efficiently and reliably. The implementation of this system involves several stages, including the installation and configuration of the Nginx server, the integration of the RTMP module, and the installation of the IP cameras in strategic locations. The video data collected was analyzed to determine the maturity level of tea leaves based on certain visual indicators. The results of this study show that the use of Nginx server with RTMP module can provide an effective and efficient solution for real-time monitoring of tea leaf ripeness, which can help farmers and tea producers in improving their quality and productivity. These findings make important contributions in the field of smart agriculture and IoT-based monitoring technologies, and open up opportunities for the development of similar systems in other agricultural contexts.